Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper focuses on structural reforms and fiscal devaluation in Italy. Italy's economy has a number of important strengths. Despite these strengths, Italy's economic performance has lagged behind its peers. The authorities' reform plans are under way in different sectors of the country. In most cases, if reforms go in the right direction, their impact would depend on consistent and prompt implementation. The model-based analysis also suggests that the potential gains to the economy from deeper reforms can be sizable.